The Effect of Gimkit Media in Discovery Learning Model on The Concept Understanding - Mustafah, Alfian; Yunus, Muh.; Side, Sumiati (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2025)
This study aims to analyze the effect of Gimkit learning media in  discovery learning model on the conceptual understanding of class XI students of SMA Negeri 9 Makassar on  material of solubility and solubility product in 2023/2024 using quasi-experimental and posttest only control group design. Population includes all class XI students with simple random sampling. XI Kimia 1 (24 students) as experimental group, while XI Kimia 3 (35 students) as control group. Independent variables use Gimkit in discovery learning and discovery learning model without Gimkit, while dependent variable is conceptual understanding as measured through cognitive learning outcomes. Instrument uses a learning outcome test. The results of descriptive analysis that average learning outcomes of experimental group are 82.87 higher than control group 78.7. Inferential analysis using Mann-Whitney Test shows Zcount> Ztable (2.00> 1.64), meaning that Gimkit in discovery learning affects students' conceptual understanding.